Protective Effects of Magnesium Biotinate on Propionic Acid-Induced Autistic Features in Rats - Komorowski, James; Ojalvo, Sara; Orhan, Cemal; Erten, Fusun; Sahna, Engin; Kilic, Ertugrul; Şahin, Kazım (Wiley, 2020)
[Abstract Not Available]
Annual Meeting on Experimental Biology -- APR 04-07, 2020 -- San Diego, CA